Case Report: Lewy body dementia with unusual psychotic symptoms, atypically late parkinsonism, and patient sensitivity to first generation antipsychotics - Lolita Ercika; Lolita Ercika; Maris Taube; Maris Taube; Maris Taube (Frontiers in Psychiatry)
Lewy body dementia is associated with abnormal eosinophilic A-synuclein neural inclusions (Lewy bodies) in the brain. It is a neurodegenerative illness—and the second most common type of dementia after Alzheimer’s disease—that causes memory loss and severe problems in carrying out daily activities. In this report, we describe a case of Lewy body dementia that began with early psychotic symptoms with atypical features (transition from hallucinosis (hallucinatory insight) to true visual hallucinations) —without Parkinsonism. The patient exhibited sensitivity to first generation antipsychotic medication, which led to a worsening of her symptoms. Physicians should consider all possible diagnoses when confronted with atypical, early symptoms of visual hallucinosis or true hallucinations and dementia without Parkinsonism. Choosing antipsychotic medicines should be made with care given these patients’ possible sensitivity to antipsychotics. The selection of antipsychotics should be consider among first, second and third generation options.